Parent–Child Relationships and Resilience Among Chinese Adolescents: The Mediating Role of Self-Esteem - Tian, Lumei; Liu, Lu; Shan, Nan (Frontiers in Psychology, 2018)
The present study primarily aimed to examine whether self-esteem serves as a mediator in the associations between parent-child relationships, including parental support and parent-child conflict, and resilience among adolescents. Three hundred four Chinese adolescents were surveyed with questionnaires and structural equation modeling was adopted to test the mediational hypothesis. The results indicated that the associations between parent-child relationships and adolescent resilience were primarily mediated by self-esteem and that parental support was more robustly linked with adolescent resilience than parent-adolescent conflict. The current study also tested a competitive mediational model in which resilience was the mediator and self-esteem was the outcome variable, and observed that this model was also well-established but inferior to the hypothesized mediational model. These findings extend our insight into the mechanisms underlying the associations among parent-child relationships, self-esteem, and resilience among adolescents and suggest that adolescent resilience promotion programs should focus on improving parental support in a family context and developing individual self-esteem.